Harmonisasi Masyarakat Multireligi Berbasis Nilai-Nilai Pendidikan Islam Moderat: Studi Etnografi di Desa Kwangengrejo Kalitidu Bojonegoro : Penelitian - Salsa Bila Zata Salwa; Muhammad Najib (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
This study aims to examine in-depth how the community of Kwangenrejo Village, Kalitidu District, Bojonegoro Regency, fosters harmony and religious tolerance in a multireligious society. Using a descriptive qualitative method and an ethnographic approach, data was collected through observations, in-depth interviews, and document studies to capture the social dynamics comprehensively. The findings reveal that harmony in Kwangenrejo Village is formed naturally and deeply rooted in the daily lives of the community. First, social interactions such as mutual cooperation, helping one another, and cross-religious visits during religious holidays reflect tangible harmony. Second, the process of building harmony is supported by an inclusive informal educational environment, such as children's involvement in their respective religious activities. Third, values of moderate Islamic education, such as tasamuh (tolerance), tawazun (balance), and ukhuwah (brotherhood), serve as a crucial foundation that fosters openness, mutual respect, and the promotion of peace amidst diversity. These findings affirm that interfaith harmony can be realized through collective awareness, values-based education, and social practices in daily life.